Promoting active learning and engagement in science with the use of gamified interactive e-learning platforms - Theodosi, Sotiroula; Nicolaidou, Iolie (My University, 2023)
This case study adds empirical data on the use of gamified e-learning platforms in K-12 by exploring 5th-grade students’ perspectives after their hands-on experience of an inquiry-based learning unit in Geography incorporating Nearpod as a delivery platform. The study’s aim was twofold: (a) to measure perceived usability, learning benefits, and engagement associated with the use of this platform (RQ1) and (b) to document students’ perceptions of interest, challenge, choice, and enjoyment (RQ2), which are key components in preserving students’ motivation in their classroom. Validated questionnaires were administered post-intervention to 30 fifth-grade students who participated in three 80-minute Geography lessons. Results revealed considerably high students’ perceptions of Nearpod’s usability, learning benefits, and engagement (RQ1). Interest and enjoyment were also perceived as high, while challenges and choices had lower scores (RQ2). These results indicate that the use of interactive e-learning platforms as delivery methods of inquiry learning content on STEM topics is beneficial for promoting students’ active learning and engagement in primary school.
Keywords: Internet of Things; Gamification; E-learning; Usability; Engagement; Motication; Nearpod